(untitled) (Research, Society and Development, 2024)
Power relations and the construction of the modern hierarchical structure influence human behavior and social groupings, in which people who identify with an ideal of belonging or collective values can interact cooperatively, collaboratively, or imposingly, to outline rules of standards of normality and superiority. Within this complex dynamic that justifies in its historical construction the designation of the object and the symbolism of the inferior or superior being, colonial relations are extracted in the determination of groups with responsibilities to teach, standardize, and colonize, in a vision of saving goodness simultaneously with the action of subjugation and devaluation of the other’s differential and groups that must behave like colonies because they are barbaric, inferior and in need of being saved to learn to evolve in knowledge and attitudes finally. This investigation aims to have a critical discussion, considering the literature and an experience report on the impact of colonial relations on the health of northeastern migrant populations and the invalidation of social health practices that seek to elevate and highlight such populations. This discussion sees the evolution of the stigma of being and working with marginalized populations.